ANALYSIS OF FINANCIAL MANAGEMENT IN AN EFFORT TO DEVELOP NURUL ABROR AL-ROBBANIYIN ISLAMIC BOARDING SCHOOL BANYUWANGI - Chindy Putri (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2023)
This study aims to understand and describe how the sources of funds and managed in the Modern Islamic Boarding School of Nurul Abror Al-Robbaniyin Banyuwangi. The research method used is aqualitative approach with descriptive analysis methods and data collection techniques through interviews, observation, and documentation. Based on the research on how the sources of funds in the Modern Islamic Boarding School Nurul Abror Al-Robbaniyin, it can be concluded as follow: 1) The sources of funds for Islamic boarding schools can be broadly classified into three sources: The government funds it in the form of BOS funds, the student parents in the form of SPP, also ZISWAF, and independent business unit in the form of Toko Yayasan Nurul Abror Al-Robbaniyin. 2) The allocation of funds is according to the regulations applied through RAPBM and recorded for each transaction. 3) The form of accountability for sources of funds is well-managed because it is made in daily, monthly, and annual reports. 4) The solution to overcome the obstacles in managing the lack of funds to run the activity is utilizing first the available sources of funds, which are sufficient because at least fulfilling the minimum needs in achieving the objectives of Islamic boarding school learning activities.